2013
DOI: 10.1890/13-0217.1
|View full text |Cite
|
Sign up to set email alerts
|

Moving to stay in place: behavioral mechanisms for coexistence of African large carnivores

Abstract: Most ecosystems have multiple predator species that not only compete for shared prey, but also pose direct threats to each other. These intraguild interactions are key drivers of carnivore community structure, with ecosystem-wide cascading effects. Yet, behavioral mechanisms for coexistence of multiple carnivore species remain poorly understood. The challenges of studying large, free-ranging carnivores have resulted in mainly coarse-scale examination of behavioral strategies without information about all inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
336
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 255 publications
(377 citation statements)
references
References 58 publications
16
336
1
2
Order By: Relevance
“…However, studies in other parts of Africa have found a much higher cub survival, even with the presence of lions (e.g., Mills & Mills, 2013). Additionally, recent research has shown that lion numbers do not negatively influence cheetah numbers (Swanson et al., 2014), which is likely because cheetahs adjust their spatiotemporal patterns on a fine scale to avoid immediate risks of these larger, more dominant carnivores (Broekhuis et al., 2013; Vanak et al., 2013). We found that cheetahs preferred areas dominated by semiclosed habitat which could explain why cheetahs preferred the wildlife areas despite the very high lion densities (Elliot & Gopalaswamy, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…However, studies in other parts of Africa have found a much higher cub survival, even with the presence of lions (e.g., Mills & Mills, 2013). Additionally, recent research has shown that lion numbers do not negatively influence cheetah numbers (Swanson et al., 2014), which is likely because cheetahs adjust their spatiotemporal patterns on a fine scale to avoid immediate risks of these larger, more dominant carnivores (Broekhuis et al., 2013; Vanak et al., 2013). We found that cheetahs preferred areas dominated by semiclosed habitat which could explain why cheetahs preferred the wildlife areas despite the very high lion densities (Elliot & Gopalaswamy, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…For example, African wild dogs Lycaon pictus move over large distances in search of habitats where they can avoid the competitively dominant lions and hyaenas, which are known to steal their kills [40]. Under scenarios of intensive interspecific competition, a dominant competitor's presence may result in avoidance of resource-rich habitats by subordinate competitors [4]. Our results show evidence of such fine-scale avoidance behaviours in one high carnivore density reserve (Nagarahole), but not in the other (Bandipur; table 5 and figure 3).…”
Section: (A) Behavioural Character Displacementmentioning
confidence: 99%
“…aggression [4]. Adaptations that facilitate intra-guild sympatry may be more pronounced as competition within the guild intensifies [9] through 'character displacement' (sensu [10]).…”
Section: Introductionmentioning
confidence: 99%
“…That is, our approach is designed to allow consideration of a wider range of landscape configurations than the square or rectangular domains such as those used in classical models of spatially explicit dynamical systems [1]. For example, our approach allows for fine-scale assessments of the behavioural response of animals to non-regular habitat edges resulting from natural disturbances due to extreme weather events or fire, or human activities [27]. Our approach allows for the entire landscape domain V to be subdivided into i different land cover or land use Figure 1.…”
Section: The Modelmentioning
confidence: 99%